Self-Regulated Learning dan Motivasi Belajar dalam Pembelajaran Matematika Secara Online: Systematic Literature Review - Veni Saputri; Dadang Juandi; Sari Herlina; Vita Nova Anwar (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
This research aims to explore and create synthesis about Self-Regulated Learning (SRL) and learning motivation in online learning. There is some research related to SRL and learning motivation as well as its impact on students' academic achievement in math learning. The search for relevant data base was conducted in a study published from 2015 to 2021 that examined SRL and learning motivation, especially in the field of mathematics education. The search strategy is done systematically by reviewing articles that have been published on the databases OF ERIC, Scopus, PubMed, Science Direct, and Google Scholar.  Based on the results of a systematic review of the literature, it was produced that SRL and motivation learning are important predictors in online math learning. In addition, SRL and learning motivation have a positive and significant influence on students' academic achievement. As for efforts to improve SRL and student learning motivation in learning can be done by applying learning that can help students develop positive values and realistic expectations for success in mathematics